Anéis de inteiros de corpos de números e aplicações - Araujo, Robson Ricardo de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This master thesis presents the rings of integers of quadratic elds, cyclotomic elds, some cyclotomic sub elds and abelian number elds aiming use them to produce algebraic lattices, which are applied in the Information Theory and in the Error Correcting Codes Theory. The text develops basic concepts about Algebra and Algebraic Number Theory, studies integral basis of number elds from two di erent perspectives, characterizes the ring of integers of the aforementioned number elds and presents some applications of this theory to algebraic lattices. The main proven theorems in this thesis are Hilbert-Speiser Theorem and Leopoldt-Lettl Theorem. The second provides the ring of integers of any abelian number eld, generalizing the rst. This thesis has a chapter dedicated to make the proof of the Leopoldt-Lettl Theorem in detail. Furthermore, this work analyses the monogenesis of some ring of integers and presents a counterexample of a ring of integers non-monogenic. The last chapter is aimed at lattices and shows examples of algebraic lattices in spaces of dimensions 2, 4, 6 and 8 constructed by ideals of ring of integers of number elds through Minkowski homomorphism. The work that created this thesis consisted mainly in research and detailing of the proofs of Leopoldt- Lettl Theorem and of three theorems linked to the issue of monogenesis of the ring of integers. This e ort created a development lighter and less compact of the proofs related to these subjects, which is presented in the text. Finally, this thesis gathers and provides a great theoretical apparatus that has been useful to development of the theory of algebraic lattices and that creates the expectation of its use in future applications in this area

Esta dissertação apresenta o anel de inteiros de corpos quadráticos, de corpos ciclotômicos, de alguns subcorpos ciclotômicos e de corpos de números abelianos com o objetivo de utilizá-los na produção de reticulados algébricos, os quais são aplicados a teoria da Informação e a teoria dos Códigos Corretores de Erros. O texto desenvolve conceitos básicos sobre Álgebra e Teoria Algébrica dos Números, estuda bases integrais de corpos de n umeros sob dois diferentes aspectos, caracteriza o anel de inteiros dos corpos de números referidos anteriormente e apresenta algumas aplicações dessa teoria aos reticulados algébricos. Os teoremas centrais demonstrados nesta dissertação são o Teorema de Hilbert-Speiser e o Teorema de Leopoldt-Lettl. Este fornece o anel de inteiros de qualquer corpo de números abeliano, generalizando aquele. Esta dissertação possui um capítulo dedicado a demonstração do Teorema de Leopoldt-Lettl de maneira detalhada. Além disso, este trabalho faz uma análise sobre a monogênese de alguns anéis de inteiros e apresenta um contraexemplo de anel de inteiros não monogênico. O último capítulo e dedicado aos reticulados e mostra exemplos de reticulados algébricos construídos nos espaços de dimensões 2, 4, 6 e 8 via o homomorfismo de Minkowski em ideais de anéis de inteiros de corpos de números. O trabalho que originou esta dissertação consistiu principalmente na pesquisa e no detalhamento das demonstrações do Teorema de Leopoldt-Lettl e de três teoremas relacionados ao tema da monogênese de anéis de inteiros. Este empenho deu origem a um desenvolvimento mais claro e menos compacto das demonstrações relacionadas a esses assuntos, o qual e apresentado no texto. Enfim, este trabalho reúne e oferece um grande aparato teórico que tem sido útil ao desenvolvimento da teoria dos reticulados algébricos e que cria a expectativa de sua utilização em futuras aplicações